Mild ovarian stimulation for in vitro fertilization: one perspective from the USA - Baker, Valerie L. (Springer US, 2013)
PURPOSE: To provide a perspective regarding mild ovarian stimulation, taking into account particular issues relevant in the United States METHODS: Literature review and editorial commentary RESULTS: Mild ovarian stimulation for IVF has some proven and some theoretical advantages over conventional stimulation, such as lower risk of ovarian hyperstimulation syndrome and lower cost per fresh IVF cycle. However, cumulative live birth rate, including transfers from fresh and frozen embryos, is likely to be lower with mild stimulation. The cost-effectiveness of mild stimulation IVF in the United States has not been established. CONCLUSIONS: Mild ovarian stimulation is an appropriate option to consider for certain patient groups or based on patient preference. However, significant potential disadvantages limit its widespread acceptability for patients in the United States at this time.